History of childhood abuse is accompanied by increased dissociation in young mothers five months postnatally - Marysko, Melanie; Reck, Corinna; Mattheis, Volker; Finke, Patricia; Resch, Franz; Möhler, Eva (Psychopathology, 2010)
Dissociation has been recognized as a relevant factor within the context of traumatization. Since childhood maltreatment as well as child birth can be regarded as a potential trauma, this study examined dissociation in a sample of 58 young mothers with a history of abuse in comparison to a control group.